SYARIAH FINTECH DALAM PERSPEKTIF MASLAHAH MURSALAH - Zainal Ach zainal anshari (STIE Mahardhika, 2023)
The increasingly developing Islamic fintech in this technological era needs to be complemented by knowledge. Therefore, this research aims to understand Islamic fintech from the perspective of Islamic law using a descriptive qualitative method. The research methodology employed in this study is a literature review gathered from various sources. The results obtained indicate that Islamic fintech has become a contemporary fiqh discourse that has not been definitively addressed in the Quran and the Hadith of the Prophet Muhammad (peace be upon him). Hence, it relies on ijma (consensus of scholars) as its legal source. The Indonesian Ulema Council issued Fatwa DSN-MUI No.117/DSN-MUI/II/2018 regarding Information Technology-Based Financing Services with Sharia Principles. This fatwa is in accordance with Islamic Sharia and has clear legal protections outlined in legislation and regulations.